КОРЕЙС ТИЛИДА “주다주다주다”주다 [CHUDA] КЎМАКЧИ ФЕЪЛИ ВА УНИНГ МАЪНОВИЙ КЎЛАМИ - Юнусова, Г. (SCIENCE and SOCIETY, 2019)
The article discusses the verb “주다” [chuda] and its features when using in the forms of respect. The author of the article also, analyzes examples of the verb “주다” [chuda] in its auxiliary meaning.